2021
DOI: 10.3390/jof7080657
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis and Risk Identification of Pulmonary Cryptococcosis in Non-HIV Patients

Abstract: Pulmonary cryptococcosis in the non-human immunodeficiency virus-infected population is uncommon. We aimed to explore the relevance between clinical presentations, radiological findings, and comorbidities and identify the outcome predictors. A total of 321 patients at Taichung Veterans General Hospital between 2005 and 2019 were included; of them, 204 (63.6%) had at least one comorbidity, while 67 (20.9%) had two or more. The most common comorbidities were diabetes mellitus (27.4%), malignant solid tumor (19.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…studies. Consistent with the previous nding [19], we found that positive baseline LFA was a risk factor for poor image outcome of PC. After antifungal therapy, the baseline LFA-negative group showed partial or complete absorption of lesions and without newly developed lesions, while the baseline LFA-positive group had a higher proportion of imaging exacerbation compared to those with weak positive LFA.…”
Section: Declarations Fundingsupporting
confidence: 92%
“…studies. Consistent with the previous nding [19], we found that positive baseline LFA was a risk factor for poor image outcome of PC. After antifungal therapy, the baseline LFA-negative group showed partial or complete absorption of lesions and without newly developed lesions, while the baseline LFA-positive group had a higher proportion of imaging exacerbation compared to those with weak positive LFA.…”
Section: Declarations Fundingsupporting
confidence: 92%
“…Those PC patients with fever had higher hs-CRP levels and larger pulmonary involvement (p < 0.05), which may indicate a risk of extrapulmonary dissemination (10). Furthermore, patients with multilobar involvement were more likely to be symptomatic as reported by Li et al (26).…”
Section: Discussionmentioning
confidence: 60%
“…We also observed that patients with SN generally presented with negative or weak positive sLFA, which is consistent with previous findings of Zhu et al ( 19 ). The serum CrAg test has a higher sensitivity in immunocompromised hosts ( 13 ), whose cryptococcal lesions are generally more serious and disseminated ( 1 , 26 ). We could not draw this conclusion due to the inadequate data of cellular and humoral immune assessment on our participants.…”
Section: Discussionmentioning
confidence: 99%
“…In HIV/AIDS, infection typically manifests with CD4 T-lymphocyte counts under 100 cells/µL [26]. Other risk factors for cryptococcal disease include solid organ transplant [27], calcineurin inhibitors and other immunomodulatory agents [28], auto-antibodies against granulocyte-macrophage-colony stimulating factor (anti-GM-CSF) [29], decompensated cirrhosis [28], type 2 diabetes mellitus, malignant solid tumours, autoimmune diseases and chronic kidney disease [30]. Pulmonary disease in all these contexts is common although dissemination has been reported to be associated with pre-existing renal impairment [31].…”
Section: Epidemiology and Host Risk Factorsmentioning
confidence: 99%